Fermented garlic extract decreases blood pressure through nitrite and sGC-cGMP-PKG pathway in spontaneously hypertensive rats. (April 2016) - Park, Byung Mun; Cha, Seung Ah; Kim, Hye Yoom; Kang, Dae Kil; Yuan, Kuichang; Chun, Hyunsoo; Chae, Soo Wan; Kim, Suhn Hee
Highlights: Fermented garlic extract (Fgarlic) contained high content of stable nitrite. Acute and chronic feeding of Fgarlic reduced SBP in SHR with increased eNOS and PKG protein expressions in aortic tissues. These effects were attenuated by sGC inhibitor. The relaxation response of aorta to acetylcholine improved in SHR fed Fgralic. Fgarlic has anti-hypertensive effect through nitrite and sGC-cGMP-PKG pathway in SHR. Abstract: Garlic ( Allium sativum L.) has long been used as an anti-hypertensive. The study investigated the effect of fermented garlic extract (Fgarlic) on systolic blood pressure (SBP) and its molecular basis using spontaneously hypertensive rats (SHRs). Fgarlic contained high content of stable nitrite (0.975 mg nitrite/ml). Acute feeding of different amounts (0.3, 0.6, and 0.9 ml) of concentrated Fgarlic (9.75 mg nitrite/ml) reduced SBP dose-dependently. Chronic feeding of Fgarlic (containing 27 mg nitrite/day) for 12 days reduced SBP with increased expressions of eNOS and PKG proteins in aortic tissues, which were attenuated by a soluble guanylyl cyclase (sGC) inhibitor. The relaxation responses of thoracic aorta to acetylcholine and sodium nitroprussside were improved in SHRs fed Fgarlic. These results suggest that nitrite in Fgarlic, which converts to NO in the body, functions as an anti-hypertensive molecule and its effect is mediated through sGC-cGMP-PKG pathway.